Woke Culture Syndrome: Is Research in Management Under Threat? - Professor Gilles Paché (Journal of Management Research, 2024)
Woke culture is spreading rapidly on North American campuses, and it is beginning to be discussed in Europe, particularly in France, within various universities. The advocates of wokism want to make people aware of the relationships of domination and social injustice induced by the political system in place. For the moment, research in management seems to escape the evils of woke culture syndrome in its most extreme manifestations (censorship, cancel culture, online harassment, etc.). The scope of this research note is to underline that the threat is credible, taking the case of research in logistics management. From a methodological point of view, an analysis of works using logistics to better understand societal phenomena allows us to identify “sensitive” topics, addressed by previous academic contributions, that may be difficult to address in the coming years under the pressure of wokism. The findings highlight two results concerning logistics: a framework for reading historical phenomena differently; and a framework for better understanding the sex industry. The main limitation is that the research note focuses only on four examples; from this point of view, perspectives are opened for a systematic analysis of the risks that wokism presents for research in management.